2008
DOI: 10.1073/pnas.0711925105
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of an U 2 S 3 -type polymorph of Al 2 O 3 at 3.7 Mbar

Abstract: We predict by first principles a phase transition in alumina at Ϸ3.7 Mbar and room temperature from the CaIrO 3-type polymorph to another with the U 2S3-type structure. Because alumina is used as window material in shock-wave experiments, this transformation should be important for the analysis of shock data in this pressure range. Comparison of our results on all high-pressure phases of alumina with shock data suggests the presence of two phase transitions in shock experiments: the corundum to Rh 2O3(II)-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 45 publications
4
53
2
Order By: Relevance
“…Several computational studies on aluminum oxide polymorphs have been reported in recent years, which mainly apply standard DFT methods. [22][23][24][25][26][27][28][29][30] In this paper, we apply a recently developed technique based on the so-called quasi-harmonic approximation (QHA): a simple and effective method that is able to address the aforementioned issue in the case of corundum. 31,32 The thermal expansion coefficient, α(T ), heat capacities, C V (T ) and C P (T ), entropy, S(T ) and bulk modulus, K(T ) of corundum are calculated in its entire range of thermal stability (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several computational studies on aluminum oxide polymorphs have been reported in recent years, which mainly apply standard DFT methods. [22][23][24][25][26][27][28][29][30] In this paper, we apply a recently developed technique based on the so-called quasi-harmonic approximation (QHA): a simple and effective method that is able to address the aforementioned issue in the case of corundum. 31,32 The thermal expansion coefficient, α(T ), heat capacities, C V (T ) and C P (T ), entropy, S(T ) and bulk modulus, K(T ) of corundum are calculated in its entire range of thermal stability (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…29,30,42 Mousavi has recently reported some quasi-harmonic thermal properties of corundum, as computed with a simplified Debye model (where the lattice dynamics of the crystal is not explicitly solved at the ab initio level of theory), which are found to largely disagree with available experimental data. 43 To the best of our knowledge, the present investigation constitutes the first complete ab initio description of thermodynamic and thermal structural and elastic properties of α-Al 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Thermal pressures on the sapphire Hugoniot to 340 GPa [13] are small relative to the calculated 300-K isotherm [21]. Shock dissipation goes into damage and disorder of the strong sapphire lattice, as well as into thermal energy.…”
Section: Experimental Datamentioning
confidence: 67%
“…[8]: solid curve, fit to experimental Hugoniot data [13]; open and solid squares, Rh 2 O 3 II-type, and CaIrO 3 -type, respectively, in DAC [14]; dotted, dashed, and dasheddotted curves, theory for corundum, Rh 2 O 3 II-type, and CaIrO 3 -type, respectively [21]. Figure 1 is plot of pressure versus compression of sapphire (i) using the linear u s -u p fit to Hugoniot data [13], (ii) measured points of sapphire compressed in a DAC, laser-heated, and thermally quenched to 300 K [14], and (iii) theoretical 300-K isotherm [21]. Static compression of corundum (α-Al 2 O 3 ) in a DAC produces only disordered corundum at all pressures.…”
Section: Experimental Datamentioning
confidence: 99%
“…It has generally been assumed since then that temperature is the mechanism of shock dissipation. The fact that entropy dominates dissipation up to 400 GPa on the sapphire Hugoniot is suggested by the fact that Hugoniot data of sapphire up to 340 GPa [19] are virtually coincident with the theoretical Hugoniot [20]. Above ~400 GPa Hugoniot pressure increases dramatically, which implies thermal pressure increases dramatically [21], which implies temperature increases dramatically.…”
Section: Sapphirementioning
confidence: 99%